On the Position of Ubi within East Chadic - Blažek, Václav (Lingua Posnaniensis, 2011)
In the article the position of a recently described East Chadic language Ubi is solved. For this aim the lexicostatistic method was used. Contrary to the classification proposed in Ethnologue16, Ubi and Mawa should be classified together with Sokoro and Barain and not together with Bidiya, Dangla, Migama, etc.